2015
DOI: 10.1038/srep07843
|View full text |Cite
|
Sign up to set email alerts
|

Reputation drives cooperative behaviour and network formation in human groups

Abstract: Cooperativeness is a defining feature of human nature. Theoreticians have suggested several mechanisms to explain this ubiquitous phenomenon, including reciprocity, reputation, and punishment, but the problem is still unsolved. Here we show, through experiments conducted with groups of people playing an iterated Prisoner's Dilemma on a dynamic network, that it is reputation what really fosters cooperation. While this mechanism has already been observed in unstructured populations, we find that it acts equally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 27 publications
2
105
0
Order By: Relevance
“…In the Trust Problem condition greater degrees of information sharing produced higher levels of honored trust (Supplementary Table 2), confirming earlier studies that found that information sharing facilitates exchange91035. However, as a result of feedback in trustee selection enabled by information sharing, these gains in trust came with increased differentiation in exchange volume.…”
Section: Resultssupporting
confidence: 85%
“…In the Trust Problem condition greater degrees of information sharing produced higher levels of honored trust (Supplementary Table 2), confirming earlier studies that found that information sharing facilitates exchange91035. However, as a result of feedback in trustee selection enabled by information sharing, these gains in trust came with increased differentiation in exchange volume.…”
Section: Resultssupporting
confidence: 85%
“…In this two-person game, players must decide whether to cooperate (C) or to defect (D) and, similarly to several recent experimental settings (e.g 1718192123…”
Section: Methodsmentioning
confidence: 99%
“…This is because participants tend to keep cooperative relationships while severing connections with defectors, and thus form cooperative and highly connected clusters in general (Rand et al, 2011). Recently, Cuesta et al (2015) showed the existence of reputation on neighbors (i.e., the history of their actions in the past a few rounds) can facilitate the emergence of cooperative clusters, and Antonioni et al (2016) further showed there existed two types of participants who are reliable subjects and cheaters when cheating her own reputation with a cost was allowed.…”
Section: Introductionmentioning
confidence: 99%